TREMATODOS DE LAS CULEBRAS DE AGUA DULCE DE MEXICO I - CABALLERO Y C, EDUARDO; C, EDUARDO (Universidad Nuevo Leon, NUEVO LEON, MONTERREY, MEX, 1941)
Some intestinal parasites of fresh water snakes of Mexico are discussed; Cercorchis kinosterni is redescribed and C thamnophidis and Renijer brevicoecum are descr
ANS INST BIOL
Keywords: TREMATODOS, CULEBRAS, AGUA DULCE, MEXICO I; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; SERPIENTES